Aplikasi Pemberian Pupuk NPK Phonska untuk Tanaman Cabai Rawit di Polybag di Kelompok Ibu-Ibu PKK RT 20 Kelurahan Pakuan Baru Kota Jambi - Hasriati Nasution; Suryanto Suryanto; Asmadi Saad; Yusfaneti Yusfaneti (WIDA Publishing, 2026)
Bird’s eye chili (Capsicum frutescens L.) is a plant that contains various bioactive compounds, including capsaicin, capsanthin, carotenoids, alkaloids, resin, and essential oils. Its growth requires adequate macro and micro nutrients, as well as enough water. One source of nutrients that can support the growth of bird’s eye chili is NPK Phonska fertilizer, which can promote strong root, larger and greener leaves, stronger stems, and more abundant fruiting. The purpose of this community service activity was to improve the skills of PKK woman in RT 20, Pakuan Baru Village, Jambi City. The results showed an increase in the participants’ knowledge and skills in cultivating bird’s eye chili.